Analysis Of User Satisfaction Towards The Telegram Application Using The EUCS (End User Computing Satisfaction) Method - Yulius Candra Akmala; I Kadek Dwi Nuryana (Universitas Negeri Surabaya, 2026)
Telegram is a messaging app that works over the cloud and focuses on being fast and secure. It has useful features like big group chats, public channels, bots, and strong security. Many people use it for talking to friends, working, and sharing information with groups. This study looked at how happy users are with Telegram and what makes them satisfied. The research used an online survey given to Telegram users who are part of the Information Systems Study Program at Surabaya State University's Faculty of Engineering. The study used a method called End User Computing Satisfaction (EUCS). The results showed that users were happy with the content (3.95), accuracy (3.91), format (3.89), ease of use (3.91), and format(3.84). The main things that really affect user satisfaction are how easy the app is to use and the format of the messages.